Ultralow emission micro-printing process for PET fibers using liquid disperse dye. Issue 5 (March 2022) - Ai, Li; Cao, Hongmei; Zhu, Yawei
The commercial powder disperse dye used for printing polyester fabrics exhibits many environmentally-unfriendly properties, especially the associated high wastewater emission. In this study, three kinds of liquid disperse dyes (C.I. Disperse Blue 291:1, (L-DB); C.I. Disperse Red 179, (L-DR), and C.I. Disperse Orange 30, (L-DO)), two kinds of binders (A and/or B), and a micro-printing process, were applied to polyester fabric, with the goal of reducing freshwater consumption while maintaining color fastness. The influences of rheological and printing performance and color fastness were studied. Home-made liquid dyes of L-DB, L-DR and L-DO were found to exhibit higher color depth, excellent color fastness, and ultralow emission of wastewater and waste residual during the micro-printing process. The binder comprised of silicone-modified polyacrylate was observed to increase dye uptake, reduce dye sublimation, and improve color fastness. The liquid dyes of L-DB, L-DR and L-DO also exhibit stable and better rheological properties, which appeared to have little effect on the viscosity of printing pastes when compared with commercial powder disperse dye of Blue 3GFL (C.I. Disperse Blue 291:1), Red 2B (C.I. Disperse Red 179) and Yellow brown S-4RL (C.I. Disperse Orange 30), respectively. Results of this micro-printing process indicated that it is an environmentally clean production technology.